Race, Housing, and the Federal Government: Black Lives on the Margins of the American Dream - Hughes, Richard (Radical Teacher, 2016)
As historians have increasingly explored the complex historical relationship between race, class, and institutions such as the federal government in shaping contemporary American society, historical sources such as the Federal Housing Association’s Underwriting Manual (1938) provide provocative opportunities for teaching. Brief excerpts from the Manual are a small window through which to examine the underappreciated role of the U.S. federal government in creating and sustaining a racialized version of the American Dream. The result is an opportunity to equip students, as citizens, with the historical thinking skills and sources to examine the enduring historical arc of racial injustice and resistance in the United States that serves as the foundation for the Black Lives Matter movement.